Validation of analytical method by HPLC for determination of dapsone in polymeric nanocapsules based on crude rice brain oil - Letícia Marques Colomé,Gaya Mengue Freitas,Janaina de Medeiros Bastiani,Thais Carla Brussulo Pereira,Lisiane Bajerski,Eduardo André Bender,Sandra Elisa Haas (Journal of Applied Pharmaceutical Science, 2017)
Dapsone is a sulfone used for the treatment of skin diseases such as psoriasis. Its clinical use by the oral route is limited. For counteract this hindrance, innovative systems based on polymeric nanocapsules containing rice bran oil and dapsone have been developed. Thus, an analytical method using HPLC for quantification of dapsone in polymeric nanocapsules based on rice brain oil was developed and validated. The separation was achieved on a C18 reverse phase column (Phenomenex, 4.6 × 150 mm, 5 μm) using a mobile phase composed of acetonitrile–1.5 % acetic acid (25:75 v/v) at a flow rate of 0.7 mL.min−1. The injection volume was 20 μL and the wavelength of detection was 230 nm. The method was linear in the range of 5-25 µg.mL−1, with a correlation coefficient of 0.9999. Precision and accuracy analysis showed low relative standard deviation (lower than 2) and recovery percentage in the range of 99.72 – 106.25%. The limits of detection and quantification were 0.41 and 1.24 μg.mL−1, respectively. The analytical method was specific, linear, precise and exact, showing that this procedure can be applied in quantification of dapsone-loaded polymeric nanocapsules based on rice brain oil.
Keywords: Dapsone, rice brain oil, HPLC,nanocapsules, photo-stability.